986 A Systematic Review of Medical Student Willingness to Volunteer and Preparedness for Pandemics and Disasters. (4th May 2021) - Byrne, M; Ashcroft, J; Alexander, L; Wan, J; Harvey, A
Abstract: Introduction: We aimed to identify motivators and barriers to volunteering during a disaster and knowledge and medical school curriculum of disaster and pandemic medicine. Method: We systematically searched the literature on 28/6/2020, following PRISMA guidelines. Results: A total of 37 studies met inclusion criteria including 11, 168 medical students and 91 medical schools. 24 studies evaluated knowledge (64.9%), 16 evaluated volunteering (43.2%), and five evaluated medical school curricula (13.5%). Weighted mean willingness to volunteer during a disaster was 68.4% (SD = 21.7%, n = 2911), and there was a significant difference between those planning to volunteer and those who actually volunteered (P<.001). We identified a number of modifiable barriers which may contribute to this difference. Overall, knowledge of disasters was poor with a weighted mean of 48.9% (SD = 15.1%, n = 2985). Conclusions: There is a large number of students who are willing to volunteer during pandemics. However, they are likely to be under-prepared for these roles due to poor overall knowledge and limited teaching. During the current COVID-19 pandemic and in future disasters, medical students may be required to volunteer as auxiliary staff. Medical schools need to develop infrastructure to facilitate this process as well as providing education and training to ensure students are adequately prepared for these roles.